2022
DOI: 10.1155/2022/8141548
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Service in the Embattled Tigray Region of Ethiopia: A Call to Action

Abstract: Haemodialysis is extremely limited in low-income countries. Access to haemodialysis is further curtailed in areas of active conflict and political instability. Haemodialysis in the Tigray region of Ethiopia has been dramatically affected by the ongoing civil war. Rapid assessment from the data available at Ayder Hospital’s haemodialysis unit registry, 2015–2021, shows that enrollment of patients in the haemodialysis service has plummeted since the war broke out. Patient flow has decreased by 37.3% from the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…The HD center which is established as a public partnership model almost a decade ago is particularly severed. Dialysis utilization has been drastically curtailed as patient enrollments in the dialysis center have decreased from 110 in 2020 (before the war) to 69 in 2021(after the war) [ 7 ]. Currently, until September 2022, there were 25 patients under suboptimal HD.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…The HD center which is established as a public partnership model almost a decade ago is particularly severed. Dialysis utilization has been drastically curtailed as patient enrollments in the dialysis center have decreased from 110 in 2020 (before the war) to 69 in 2021(after the war) [ 7 ]. Currently, until September 2022, there were 25 patients under suboptimal HD.…”
Section: Main Textmentioning
confidence: 99%
“…Patients with otherwise treatable kidney failure are dying. Overall, the percentage of mortality in patients receiving HD has doubled from 25.5% before the war to 53.1% after the war broke out [ 7 ]. The severe symptoms of suffering patients and the inevitable preventable death in front of the attending healthcare workers lead to vicarious trauma.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The siege brought a humanitarian aid blockade, lack of transportation fuel, power outages, communications blackouts, and banking services interruption, and it depleted all essential drugs and medical supplies. [7][8][9][10] After 20 months, displacement, death, and destruction had become the defining elements of this war, putting millions of lives at risk. An assessment by Médecins Sans Frontières (Doctors Without Borders) concluded that of the 106 health facilities, nearly 70% were looted and more than 30% were damaged from mid-December through early March 2021 in a deliberate and widespread attack on health care; just 13% were functioning normally.…”
mentioning
confidence: 99%
“…Ayder Comprehensive Specialized Hospital ( Fig. 2 ), the main hospital in the Tigray region, which was relatively spared from looting and destruction, is now unable to provide basic medical care because of lack of essential medical supplies ( Berhe et al, 2022 , Wall, 2022 ). Before the war broke out, Ayder served as a specialized referral center for a catchment area of 9 million people from Tigray, and neighboring districts of the Afar and Amhara region.…”
mentioning
confidence: 99%